Rancang Bangun Prototype Pemotong Rumput Berbasis Arduino Uno Dengan Kendali Smarphone Android - Novita, Tria; Chandra, Yudi; Rozie, Fachrul (Electrical Network Systems and Sources, 2024)
Maintaining a clean environment has become an individual responsibility, but maintaining it requires more time, energy and costs. In this research, the aim is to design a prototype grass cutter based on Arduino Uno with remote control using an Android smartphone with a Bluetooth connection to avoid the risk of accidents that could occur. The process of designing a grass cutter prototype based on an Arduino Uno with Android smartphone control is problem identification, data collection, tool design, tool making, testing, discussion and conclusions. In the process of designing a grass cutter prototype based on an Arduino Uno with Android smartphone control, selecting the required components, then calculating the required components. After the type and specifications of the components are known, the next step is to calculate the manufacture of a prototype grass cutter based on an Arduino Uno to find out the recommended Cost Budget (RAB) for a prototype grass cutter based on an Arduino Uno with Android smartphone control. The test results show that this system can operate well, is able to detect and provide effective grass cutting performance and the Bluetooth module used as a controller connection functions with a control distance of 1 meter to 20 meters. The height of the grass that can be cut by the prototype grass cutter is 5 cm to 15 cm. The test results show that battery consumption in 1 minute when the grass cutter prototype is operating is 0.8 Volts, then after using it for 5 minutes there is a reduction in battery voltage from 15.05 Volts to 11.05 Volts, meaning that after 5 minutes of use there is a current consumption of 4 Volts and the system will stop operating when the voltage drops below 12 V. Keywords: Prototype, Grass Cutter, Arduino Uno, Android Smartphone, Bluetooth HC-06.